Effect of soil management system and fertilization level on sunflower cultivated after Avena strigosa - Ferreira da Silva, Paulo Regis; Wendt, Wilson; Brondani da Rocha, Andréa (Pesquisa Agropecuaria Brasileira, 1997)
Direct seeding and the planting of winter crops for soil cover are techniques which have acquired importance in maintaining or increasing productivity of summer crops. The objective of this study was to determine the effect of soil management systems (conventional and direct planting), and fertilization levels (zero, half and recommended doses of N, P2O5, K2O and B) in sunflower (Helianthus annuus L.) culture in two cultivation systems preceeding the culture (with Avena strigosa or in fallow). The experiment was carried out in the 1990/91 and 1991/92 growing seasons, in the EEA/UFRGS, in the Central Depression of Rio Grande do Sul. Grain yield of sunflower and the leaf nitrogen content were affected by the fertilization level, being smaller in the treatments without fertilization. Data relative to stem diameter, plant stature and root length showed that the sunflower plants presented greater growth in the conventional soil management system, and in succession to Avena strigosa.